TAKONEO-MESSAGING SYSTEM SEBAGAI PELAYANAN KEBIDANAN SELAMA PANDEMI COVID-19: Takoneo-Messaging System As A System Of Midwifery Service In Neonates During The Covid-19 Pandemic - Niken Grah Prihartanti; Mudhawaroh; Septi Fitrah Ningtyas (LPPM - STIKES Pemkab Jombang, 2022)
Background: Midwifery services are very limited in frequency by health workers, mothers are reluctant to visit health facilities because they are worried. Researchers created the Takoneo-Messaging System to support the health of neonates during the COVID-19 pandemic. Aim: To identify the effectiveness of the Takoneo Message System in the mentoring of the neonatal period. Methods: Researchers used a qualitative research approach, and carried it out from February to May 2021. The stages carried out in this study included program design; research ethics; selection of subjects; and data collection using interview and observation techniques. This study involved 16 subjects consisting of 2 midwives, 7 midwifery students, and 7 mothers who had babies aged 0-28 days. Results: Almost all subjects involved in this study or as much as 94% supported the development of Takoneo. Conclusion: Utilization of the Takoneo-Messaging System can overcome the problem of sustainable midwifery care assistance services during the neonate during pandemic.